Application of Deterministic Simulation Modeling for Capital Structure Robustness Testing: A Case Study in the Capital-Intensive Industry (AGII) - Legiman Samosir; Haikal Habibi Siregar (Journal of Information Technology and Computer System, 2026)
In the capital-intensive sector, the strategic management of capital structure is often constrained by cost rigidity, where high fixed costs magnify the impact of demand volatility on corporate solvency. This study addresses the methodological gap in static financial analysis by applying Deterministic Simulation Modeling to conduct a Robustness Test on PT Aneka Gas Industri Tbk (AGII). The primary objective is to measure the structural resilience of the firm against operational shocks specifically demand fluctuations attributed to the bullwhip effect and to evaluate the efficacy of refinancing as a risk mitigation strategy. Using audited financial data, the simulation executes specific "what-if" scenarios to project changes in Net Income, Interest Coverage Ratio (ICR), and Financial Distress probability based on the Springate S-Score. The empirical results reveal a significant structural vulnerability: a moderate revenue decline of 5% plunges the baseline performance into a net loss of IDR 5,027 million, confirming the detrimental impact of high operating leverage. However, the simulation demonstrates that a strategic refinancing intervention, reducing the cost of debt from 8.1% to 6.75%, effectively transforms the company’s risk profile from fragile to robust. This optimization not only maintains profitability under stress but also significantly lowers the Break-Even Point (BEP), thereby widening the Margin of Safety. The study concludes that deterministic simulation offers a superior, forward-looking framework for management to identify financial "breaking points" and implement proactive liability management to ensure sustainability amidst economic uncertainty.